THE MODEL OF PROJECT-BASED AND COGNITIVE COMPETENCIES-INFUSED LEARNING IN THE GRAMMAR CLASS OF ELESP: MODEL OF PROJECT-BASED AND COGNITIVE COMPETENCIES-INFUSED LEARNING IN THE GRAMMAR CLASS OF ELESP - Oktavyana, Annisa; Sulistyaningrum, Siti Drivoka; Dewanti, Ratna (BASIS (Bahasa dan Sastra Inggris), 2022)
Model of learning is a guideline that teachers will use to let their teaching more comprehensive and practical to facilitate the achievement of the learning goal. A dynamic approach suited to teaching in which students explore real-world problems and challenges, simultaneously developing 21st-century skills while working in small collaborative groups is Project-Based Learning. The purpose of the study is to analyze the used model of Project-Based and Cognitive competencies-infused learning in the grammar class of English Language Education Study Program. This study employed a qualitative design where the data are the components of the existing models of learning in grammar classes of English Language Education Study Program. Besides, online class observation and grammar class syllabus documents are used as instruments. The findings of analysis revealed that Methods that generally used in the online class observation are Computer-Assisted Instruction (CAI), Scaffolding, Reciprocal method, Cooperative Learning while mostly used Lecturing, General Discussion, and Presentation to delivering material. The indicator that could be seen in syllabus document and class observations was Critical Thinking from Cognitive competences indicators. The Project-Based Learning indicators could also be seen directly from syllabus documents and online class observations. Intellectual Challenge and Accomplishment was mostly dominated seen in the model.